Adaptation Atlas Notebook: Formulate a climate rationale for projects / Formuler une justification climatique pour les projets - Steward, Peter; Youngberg, Brayden; Ramirez Villegas, Julian; Achicanoy, Harold; Vyas, Shalika; Rosenstock, Todd (2025)
This notebook helps users build strong, evidence-backed climate rationales for agricultural adaptation projects in Africa. It brings together key datasets on population, poverty, land use, GDP, and heat stress to characterize baseline conditions and identify climate-related vulnerabilities at national and subnational levels. Users can interactively explore exposure to extreme heat, demographic pressures, and economic structures, then combine these insights into a coherent narrative explaining why adaptation investments are needed. By integrating climate risks with socio-economic context, the notebook supports the development of compelling, data-driven justifications for funding proposals and project design.